ARSITEKTUR SOFTWARE AS A SERVICE (SAAS) PADA LAYANAN RUMAH SAKIT - Toni Kusnandar (STMIK Mardira Indonesia, Bandung, 2015)
Cloud Computing is a trend that includes several categories of services, all offered in the form of an Internet service with a model pay for what is used by the user (pay as you go). Software as a Service (SaaS) is one in this category, in addition to Platform as a Service (PaaS) and Infrastructure as a Service (IaaS). SaaS is the most mature category of Cloud Service, as evolved from the model application service-provider. Hospital as an institution that provides service every day of non-stop for 24 hours, began requiring the application of Cloud Computing to save operating costs of data processing, improve agility, but still can involve a lot of users. Therefore we need an appropriate architecture to meet the expectations of the Hospital. SaaS architecture in hospital services will contribute to the Data Architecture, Application Architecture and Technical Architecture will even contribute also to the Organizational Architecture. Keywords: Cloud Computing, Software as a Service